(untitled) (Journal of Faculty of Education, 2021)
Aspergillus niger spores were isolated from diseased Striga plants at the Demonstration Farm Faculty of Agriculture, Shambat was used as a mycoherbicide for the biocontrol of Striga hermothica plant. Sterilized dried sorghum straw, Alfalafa hay and sucrose were used, as solid state substrates for growth and multiplication. These were used in different formulations coated to sorghum seeds or mixed with soil or added after Striga emergence to spores of Aspergillus niger . The results indicated that the formulation camposed of %07 sterilized sorghum straw , %57 alfalfa hay formulation and 57 sucrose was the best as it yielded the highest number of spores as compared to other formulations. Therefore, this formulation was selected for further application and was applied for inoculation of Striga seeds in the presence of its host (sorghum) seeds in different ways in the glass house at Shambat, Faculty of Agriculture.